Effect of dilutors on extracellular enzyme activity of preserved boar semen - PANDEY, R P; SINGH, B K (The Indian Journal of Animal Sciences, 2014)
Seminal plasma samples (325) of undiluted, freshly diluted, and preserved boar semen of 24, 48 and 72 hr with 3 diluters were used to estimate the variation in extra-cellular level of aspartate amino transferase (AST), alanine amino transferase (ALT), lactic dehydrogenase (LDH) and alkaline phosphatase (AKP). Mean value ofaspartte amino transferase, alanine amino transferase, lactic dehydrogenase and alkaline phosphatase in neat semen was 99.640, 16.640, 689.20 IU/109 sperms and 397.533 AK units/100 ml of semen respectively. The effect of sire on extracellular activity of AST, LDH and AKP was highly significant. Nonsignificant effect of sire on extracellular activity of ALT was recorded in neat semen. The effect of dilutors on the acti vity of both AST and ALT was observed significant at 24, 48 and 72 hr of preservation. The influence of dilutors on extracellular activity of LDH was observed at 48 and 72 hr of preservation, showing the maximum increase with BL-1 dilutor (1461.92 Â± 0.927 units/l09 sperms). Higher value of AKP (403.936 Â± 9.279) was observed with BL-1 dilutor in freshly diluted semen, which decreased significantly with increase in preservation time. Highly significant (P< 0.01) effect of both hours of preservation and dilutors was observed on extracellular activity of these enzymes.